2021
DOI: 10.1002/jcop.22602
|View full text |Cite
|
Sign up to set email alerts
|

Mental health service utilization among African immigrants in the United States

Abstract: This study utilized Andersen's model of health behavior to explore factors associated with mental health service utilization. We also examine rates for mental health service use, treatment preferences, and barriers to care. Data were collected utilizing web-based surveys. The sample consisted of first and second-generation African immigrants who had struggled with emotional or behavioral problems in the past 12 months (N = 323). Hierarchical logistic regression analyses were conducted to examine predictors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Prior evidence from a double-blinded randomized controlled trial has demonstrated that high stress leads to low post-meal energy expenditure, which favors the development of overweight and obesity [ 41 ]. Migrants are exposed to different stressors, including financial stressors, the fear of deportation, acculturation stress, being far from their family and loved ones, language barriers, and so on [ 42 , 43 , 44 ]. An additional challenge for African immigrants living in the US is that they have lower utilization of mental health services despite a greater need for those services [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior evidence from a double-blinded randomized controlled trial has demonstrated that high stress leads to low post-meal energy expenditure, which favors the development of overweight and obesity [ 41 ]. Migrants are exposed to different stressors, including financial stressors, the fear of deportation, acculturation stress, being far from their family and loved ones, language barriers, and so on [ 42 , 43 , 44 ]. An additional challenge for African immigrants living in the US is that they have lower utilization of mental health services despite a greater need for those services [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migrants are exposed to different stressors, including financial stressors, the fear of deportation, acculturation stress, being far from their family and loved ones, language barriers, and so on [ 42 , 43 , 44 ]. An additional challenge for African immigrants living in the US is that they have lower utilization of mental health services despite a greater need for those services [ 44 , 45 ]. These stressors could not only interfere with the African immigrants’ ability to maintain healthy weight management practices but also alter their food metabolism, leading to weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of trust can influence any step of a research project, from fear of being identified as an immigrant and being asked to answer invasive questions to fear that someone in their community might be identified through the dissemination of findings (Kass et al, 1996; Mastroianni, 2008). Saasa et al (2021) modified their question around immigration status to ask participants about how they entered the United States rather than asking them about their visa type to encourage participation. Similar questions can be employed in research with immigrants.…”
Section: Barriers To Research Successmentioning
confidence: 99%
“…One study reported differences in severity of depression based on gender and migrant status for African immigrants; the authors found that second generation immigrants had lower depression among men compared to first generation immigrants [ 16 ]. Saasa and colleagues’ study showed African male immigrants used mental health services less frequently than African female immigrants [ 17 ]. Most studies, however, relied largely on qualitative methods and the sample in Saasa and colleagues’ study was predominantly female [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saasa and colleagues’ study showed African male immigrants used mental health services less frequently than African female immigrants [ 17 ]. Most studies, however, relied largely on qualitative methods and the sample in Saasa and colleagues’ study was predominantly female [ 17 ]. Psychosocial factors such as stigma behavior, the burden of medical mistrust, and stress related to racism are known contributors to psychological distress and depression symptoms for Black people [ 18 ].…”
Section: Introductionmentioning
confidence: 99%